A universal rig for supporting large hammer drills: Reduced injury risk and improved productivity. (October 2015) - Rempel, David; Barr, Alan
Highlights: A rig for supporting large hammer drills was developed using a participatory process. Key safety features were reduced hand forces and vibration and effective dust capture. The final design improved usability and reduced fatigue compared to conventional drilling. Drilling time with the rig was reduced by 50%. Abstract: Drilling holes into concrete with heavy hammer and rock drills is one of the most physically demanding tasks performed in commercial construction and poses risks for musculoskeletal disorders, noise induced hearing loss, hand arm vibration syndrome and silicosis. The aim of this study was to (1) use a participatory process to develop a rig to support pneumatic rock drills or large electric hammer drills in order to reduce the health risks and (2) evaluate the usability of the rig. Seven prototype rigs for supporting large hammer drills were developed and modified with feedback from commercial contractors and construction workers. The final design was evaluated by laborers and electricians ( N = 29) who performed their usual concrete drilling with the usual method and the new rig. Subjective regional fatigue was significantly less in the neck, shoulders, hands and arms, and lower back when using the universal rig compared to the usual manual method. Usability ratings for the rig were significantly better than the usual method on stability, control, drilling, accuracy, and vibration. Drilling time was reduced by approximately 50% with the rig. Commercial construction contractors, laborers and electricians who use large hammer drills for drilling many holes should consider using such a rig to prevent musculoskeletal disorders, fatigue, and silicosis.